2012
DOI: 10.1097/pai.0b013e318223ef29
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Lymphoma-associated Macrophages in Tumor Tissue Is an Independent Prognostic Factor in Patients With Follicular Lymphoma

Abstract: The clinical course of patients with follicular lymphoma is variable from a slowly progressive disease to a progressive disease with a survival time of approximately 1 year. Many prognostic models have been suggested to identify high-risk patients. Recent gene profiling analysis showed that the clinical behavior of follicular lymphoma is determined by the properties of the nonmalignant tumor microenvironment. We investigated the role of lymphoma-associated macrophages (LAMs) in tumor tissue in patients with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The immunohistochemical expression of CD68 (an indicator of TAM infiltration) and the co‐expression of CD68 with CD163 (an indicator of a specific subset of TAM), have been shown in some (but not all) studies to predict the outcome of HL, FL and DLBCL (Farinha et al , ; Kelley et al , ; Taskinen et al , ; Canioni et al , ; Hasselblom et al , ; de Jong et al , ; Steidl et al , ; Wahlin et al , ; Andjelic et al , ; Azambuja et al , ; Cai et al , ; Wada et al , ; Greaves et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunohistochemical expression of CD68 (an indicator of TAM infiltration) and the co‐expression of CD68 with CD163 (an indicator of a specific subset of TAM), have been shown in some (but not all) studies to predict the outcome of HL, FL and DLBCL (Farinha et al , ; Kelley et al , ; Taskinen et al , ; Canioni et al , ; Hasselblom et al , ; de Jong et al , ; Steidl et al , ; Wahlin et al , ; Andjelic et al , ; Azambuja et al , ; Cai et al , ; Wada et al , ; Greaves et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…but signatures associated with monocytes, macrophages and dendritic cells may have a significant impact on survival in other lymphoma types, including follicular lymphoma (FL) (Dave et al, 2004), diffuse large B cell lymphoma (DLBCL) (Lenz et al, 2008) and classical Hodgkin lymphoma (HL) (Steidl et al, 2010). The immunohistochemical expression of CD68 (an indicator of TAM infiltration) and the co-expression of CD68 with CD163 (an indicator of a specific subset of TAM), have been shown in some (but not all) studies to predict the outcome of HL, FL and DLBCL (Farinha et al, 2005;Kelley et al, 2007;Taskinen et al, 2007;Canioni et al, 2008;Hasselblom et al, 2008;de Jong et al, 2009;Steidl et al, 2010;Wahlin et al, 2010;Andjelic et al, 2012;Azambuja et al, 2012;Cai et al, 2012;Wada et al, 2012;Greaves et al, 2013).…”
Section: Variablementioning
confidence: 99%
“…With regard to follicular lymphoma, six studies showed a significant association between a poor clinical prognosis and a high density of CD68 + TAMs, and three other studies showed that a high density of TAMs was associated with a good clinical prognosis . Some researchers compared the number of TAMs in intrafollicular and perifollicular areas and studied the associations between TAMs in these areas, but the clinical prognoses in these studies differed . Just one study noted the significance of CD163 for TAMs in follicular lymphoma .…”
Section: Tams In B‐cell Lymphomamentioning
confidence: 99%
“…In this article, the absolute monocyte count (AMC) at diagnosis was identified as an independent predictor for survival when compared with the Mantle Cell Lymphoma International Prognostic Index (MIPI). The postulated mechanism for this relationship is that AMC is a surrogate biomarker of the tumour microenvironment by reflecting the recruited peripheral blood immuno‐suppressive monocytes (Wilcox et al , ; Lin et al , ) by the tumour transforming into tumour‐associated macrophages, leading to cancer progression (Hasseblom et al , ; Andjelic et al , ). Given their observation, we analysed our own institutional data to explore if AMC at diagnosis predicts overall survival and progression‐free survival in mantle cell lymphoma patients.…”
Section: Baseline Characteristics Based On the Absolute Monocyte Counmentioning
confidence: 99%